2008
DOI: 10.1021/jf8017029
|View full text |Cite
|
Sign up to set email alerts
|

Absorption, Uptake and Tissue Affinity of High-Molecular-Weight Hyaluronan after Oral Administration in Rats and Dogs

Abstract: The purpose of this study was to determine the absorption, distribution and excretion of 99m technetiumlabeled, high-molecular-weight hyaluronan (( 99m Tc-P. Urinary and fecal excretion after 99m Tc-HA ingestion by rats showed 86.7-95.6% of radioactivity was recovered, almost all in feces. All tissues examined showed incorporation of radioactivity from 99m Tc-HA starting at 15 min and persisting for 48 h, in a pattern significantly different from 99m Tc-P. Wholebody scintigraphs and close-ups of the ventral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
103
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(114 citation statements)
references
References 31 publications
(66 reference statements)
3
103
0
4
Order By: Relevance
“…It has been reported that the absorption efficiency of polysaccharides increased with the decrease of molecular weight (Balogh et al, 2008;Zeng, Qin, Wang, Chi, & Li, 2008). In the present study, the improvement of antiproliferative activity might be due to the decreased molecular weight of CSPS-1 after sulfation.…”
Section: Antitumor Activities Of Csps-1 and Csps-1-ssupporting
confidence: 50%
“…It has been reported that the absorption efficiency of polysaccharides increased with the decrease of molecular weight (Balogh et al, 2008;Zeng, Qin, Wang, Chi, & Li, 2008). In the present study, the improvement of antiproliferative activity might be due to the decreased molecular weight of CSPS-1 after sulfation.…”
Section: Antitumor Activities Of Csps-1 and Csps-1-ssupporting
confidence: 50%
“…Because of transport issues with higher molecular weight hyaluronan, the lower molecular weight GS and CS are more effective tracers. 7 Chondrocytes use GS for CS synthesis. Non-labeled native GS has therapeutic applications in osteoarthritis (OA) and radiolabeled GS was initially developed for scintigraphic detection of OA.…”
Section: Nuclear Imaging (Table 9)mentioning
confidence: 99%
“…In der Synovialflüssigkeit bewirkt sie eine Reibungsverminderung auf den artikulierenden Knorpeloberflächen. Die grundsätzliche Frage, ob die orale Einnahme bei einem sehr hohen First-passEffekt überhaupt das Gelenk erreichen kann, wurde durch eine Tierstudie mit radioaktiv markierter Hyaluronsäure positiv beantwortet [5]. Für die klinische Anwendung sind nur wenige Studien mit einer geringen Evidenz publiziert.…”
Section: Hyaluronsäureunclassified